Cassava mosaic virus disease pandemic - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Cassava mosaic virus disease (CMD) is so prevalent in some countries that it is regarded as a normal feature of cassava plants; little attempt is made to control the disease and impaired, sub-standard yields are accepted as normal. There are no...